Mapping reduced introgression loci to the X chromosome of the hybridizing field crickets, Gryllus firmus and G. pennsylvanicus - Gainey, D. Patrick (PLoS One, 2018)
The genomic architecture of barriers to gene exchange during the speciation process is poorly understood. The genomic islands model suggests that loci associated with barriers to gene exchange prevent introgression of nearby genomic regions via linkage disequilibrium. But few analyses of the actual genomic location of non-introgressing loci in closely related species exist. In a previous study Maroja et al. showed that in the hybridizing field crickets, Gryllus firmus and G. pennsylvanicus, 50 non-introgressing loci are localized on two autosomal regions and the X chromosome, but they were not able to map the loci along the X chromosome because they used a male informative cross. Here, we localize the introgressing and non-introgressing loci on the X chromosome, and reveal that all X-linked non-introgressing loci are restricted to a 50-cM region with 10 of these loci mapped to a single location. We discuss the implications of this finding to speciation.